It is only fair: blood donors are more sensitive to violations of fairness norms than nondonors – converging psychometric and ultimatum game evidence. Issue 3 (9th February 2018) - Ferguson, E.; Lawrence, C.
Abstract : Background and Objectives: The design of effective donor recruitment campaigns requires an accurate understanding of donor motivations. This requires cross‐validation of theoretically derived, psychometrically assessed motivations with behavioural preferences. Theoretical models suggest that blood donors should be more sensitive than nondonors to violations of fairness norms. Specifically, active blood donors, compared to nondonors, should endorse beliefs of reciprocal fairness, norms of both positive and negative reciprocity and reject more unfair offers in a behavioural economic game (the ultimatum game). This study is the first to test this hypothesis. Materials and Methods: Two studies are reported. One experimental psychometric study ( N = 400) and one behavioural economic game using the ultimatum game ( N = 60). Results: Consistent with the predictions, active and lapsed donors, compared to nondonors, were more likely to endorse beliefs of reciprocal fairness and active donors to endorse norms of both positive and negative reciprocity and reject more unfair offers in the ultimatum game. This pattern of motivations was unique to blood donors and not observed for other health (i.e. being on the organ donor register) and nonhealth (e.g. volunteering) prosociality. Conclusion: Blood donors have a heightened sensitivity to unfairness violations. This indicates a very clear and specific line for the development of interventions that align fairness, self‐interest and reciprocity, for example voluntary reciprocal altruism (VRA). We also highlight the importance of establishing intervention development within a clinical trials model and emphasize why experimental work of this type is vital.